Aplikasi POC Daun Kelor Dan Pupuk Kandang Ayam Terhadap Pertumbuhan Dan Hasil Bawang Merah (Allium ascalonicum, L) : POC daun kelor; pupuk kandang ayam; bawang merah - Regina Ayu Andini; Priyono, Priyono; Siswadi, Siswadi (innofarm, 2023)
To Fulfill soil nutrients can be done by providing organic and inorganic fertilizers, but use of inorganic materials can damage the soil due to contamination of chemicals. Therefore, this research was conducted to analyze the effect of moringa leaf LOF and chicken manure fertilizer on the growth and yield of shallot plants. This study used a Completely Randomized Block Design (RAKL) which consisted of 2 treatment factors which each factor consisted of 3 levels and was repeated 3 times. The first factor was the concentration of moringa LOF: K0 (control), K1 (200 ml/l) and K2 (400 ml/l). The second factor is: P0 (control), P1 (40 g/plant) and P2 (80 g/plant). Observational data were analyzed using analysis of variance (ANOVA) and continued with the BNT test with a level of 1%. Parameters observed included, number of leaves, plant height, tuber fresh weight, number of tubers clumping, tuber diameter and tuber dry weight. The results showed that the best treatment, is dosing of chicken manure dose of 10 tonnes/ha with a fresh tuber weight yield of 28.53 g/plan or 7.13 tonnes/ha and a dry tuber weight of 21.83 g/plant or 5.46 tonnes/ha.